The Influence of Zinc Biofortification on the Growth, Yield, and Zinc Content in Several Rice Varieties (Oryza sativa L.) - Kholfira Masoyogie; Muhammad M Kamal; Eko Pramono; R A Diana Widyastuti; Muhammad Syamsoel Hadi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Rice productivity faces challenges due to soil degradation and nutrient deficiencies. This study aims to evaluate the effects of zinc (Zn) biofortification through foliar spray on growth, yield, potassium (K) uptake, and zinc (Zn) content in rice grains. The study also assesses the response of different rice varieties to zinc application and analyzes the interaction between zinc and varieties in enhancing productivity and zinc content, which could potentially support stunting prevention efforts. The research was conducted in the rice fields of Maja Village, Pesawaran Regency, Lampung, from July to October 2024, using a split plot design. Zinc treatments included seed priming and foliar spray at the vegetative and generative stages. The results showed that zinc application significantly increased plant height, productive tillers, flowering time, number of grains per panicle, percentage of filled and empty grains, 1,000-grain weight, as well as harvest dry grain (HDG) and dry unhusked rice (DUR). Treatment P4 (priming and zinc application at both vegetative and generative stages) showed the best response, with an average increase in zinc content in rice grains of 56% compared to the control. Nutri Zinc variety showed the highest potassium uptake and zinc content. The interaction between zinc and variety had a significant impact on 1,000-grain weight and HDG. This study highlights that zinc biofortification can improve rice production and increase zinc content in rice, supporting stunting prevention.